2022
DOI: 10.1007/s10479-022-04528-3
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning-based approach for performance assessment and prediction: A case study of pulp and paper industries

Abstract: The pulp and paper industry is critical to global industrial and economic development. Recently, India's pulp and paper industries have been facing severe competitive challenges. The challenges have impaired the environmental performance and resulted in the closure of several operations. Assessment and prediction of the performance of the Indian pulp and paper industry using various parameters is a critical task for researchers. This study proposes a framework for performance assessment and prediction based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In general, AI-based neural network algorithms have been demonstrated to be an excellent predictive tool (Patel et al 2017), as evidenced by particle size prediction (Gautam et al 2021), equipment effectiveness prediction (Sivakumar et al 2022), and paper industry performance prediction (Jauhar et al 2022). Likewise, the robust search algorithm of Back Propagation Neural Network (BPNN) also a good technique for predicting facilities (Zhang and Qu 2021).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…In general, AI-based neural network algorithms have been demonstrated to be an excellent predictive tool (Patel et al 2017), as evidenced by particle size prediction (Gautam et al 2021), equipment effectiveness prediction (Sivakumar et al 2022), and paper industry performance prediction (Jauhar et al 2022). Likewise, the robust search algorithm of Back Propagation Neural Network (BPNN) also a good technique for predicting facilities (Zhang and Qu 2021).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Previous research has shown that the complementary features of DEA with ANN integration can be built into a promising integrated model (e.g. Misiunas et al, 2016;Rezaee et al, 2018;Jauhar et al, 2022;Pratap et al, 2022). Athanassopoulos and Curram (1996) were the first to exploit the corresponding properties of DEA and ANN.…”
Section: The Efficiency Of Canadian Universitiesmentioning
confidence: 99%
“…More publications and studies exist on e-commerce customer segmentation regarding return products and their attitudes toward purchase behavior (Ma, 2022). From this vantage point, we propose a digital transformation-based approach that assesses whether RFM segmentation analysis can enhance consumer segmentation (Pratap et al ., 2022; Jauhar et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%